The role of marine and diving authorities in workforce development in the blue economy - Nisa, Zahidah Afrin (Frontiers in Marine Science, 2022)
Island governments have made decent work and social protection their highest policy priority, aiming to link them to the so-called blue economy sectors such as fisheries. The development of small-scale commercial fishing is primarily driven by transnational fisheries trade and depends on dive fisher labour force facing issues with deficits in decent work, health and safety, and safety at sea provisions. Given the macro-policy priorities for decent work in the transition of small island developing states (SIDS) to blue economy, this paper examines the development interventions in small-scale commercial fisheries trade that have exacerbated unsafe marine working conditions of dive fishers. Despite significant investments in developing commercial fisheries trade, the mismatch between macro-level decisions and micro-level labour needs has hardly been explored via the blue economy and sustainable development goal interlinkages. This study used a qualitative research approach to examine the unsafe working conditions of dive fishers and examined why dive-related accidents and fatalities occur in commercial fisheries in the first place. A systematic approach in the analysis of diving accidents helps the study to, firstly, highlight the gaps between macro policy and practice at the national and global levels. Secondly, the approach helps explore the need for a coherent approach to policy integration that bridges the gap between the macro and operational levels of small-scale fisheries labour force. The study analyses the International Labour Organization’s decent work instruments with SIDS sustainable development priorities for fisheries workforce and points out that governments must be responsible at the macro level for managing accidents at sea and building a safe diving workforce through competent marine and diving authorities.